Using Project-Based Learning Model to Promote Students’ Listening Comprehension at Vocational High School - Ratih Krisnoviani; Sulistyani Sulistyani (EDUKATIF : JURNAL ILMU PENDIDIKAN, 2022)
This research aims to determine whether there is an influence or not from students’ learning achievement on listening comprehension skills using a project-based learning model. In this research, the researcher used a quantitative approach, using an experimental method, which is a pre-experimental design with a one-group pre-test and post-test model. The data collection used pre-test and post-test instruments by applying the purposive sampling technique, with a student population of 31 eleventh grade students of multimedia majors. Analysis of the data used a two-sample independent t-test with a significant p > 0.05. The students’ learning outcomes showed an increase, with an average value of 75.68. The data analysis shows the result of sig. (2-tailed) 0.00 < 0.05, it can be concluded that there is a significant effect of the implementation of the project-based learning model on the listening comprehension skills. This research has benefits in developing a project-based learning model, especially in listening skills